Economic Sustainability of the Cikolelet Tourism Village Community : A Review of the Effectiveness of The Village-Owned Enterprise Organization - Azizah, Felia; Rahmawati, Rahmawati; Yusuf, Maulana (Indonesian Journal of Social Science Research, 2026)
Village-owned enterprises in tourism villages play a central role in community economic development. BUMDes can act as tourism operators or serve as a platform for small and medium-sized enterprises (SMEs) that produce tourism-related products. However, BUMDes are still considered ineffective as village government units in community economic development. This is due to voluntary membership among managers and a lack of understanding regarding tourism promotion or tourism products. This study aims to measure the effectiveness of BUMDes in Cikolelet Village. The research method used is descriptive quantitative analysis with the population of Cikolelet Village. Data collection used a primary questionnaire and included in-depth interviews with key informants. The research results indicate that BUMDes in Cikolelet Tourism Village are deemed sufficiently effective in boosting the village economy. Based on the hypothesis test results, the value was 57%. This is lower than the previous researcher's result of 61%, or the calculated t-value is smaller than the critical t-value (-3.415 < 1.661). This means the null hypothesis (H0) is accepted, and the alternative hypothesis (Ha) is rejected. Interview results reinforce this finding. BUMDes Cikolelet has not established a new management structure due to a lack of human resources with expertise in BUMDes administration. Additional challenges include the absence of collaboration with external parties, insufficient development and mentoring of MSMEs, an inability to adapt to changes, and a lack of innovation for BUMDes development.